Unveiling Global Trends in Coronary Heart Disease Research: A Scopus Bibliometric Analysis - Qonita Sari Bustomi; Salma Fathinah; Nurul Ilma Haryono; Rian Ka Praja (Al-Musthalah: Jurnal Riset dan Penelitian Multidisiplin, 2024)
The heart stands as a critical organ within the human body, susceptible to various disorders with distinct characteristics. Notably, coronary heart disease, due to its escalating worldwide prevalence, commands significant attention. However, this disease is not restricted to a specific age group and can afflict those not adhering to healthy lifestyles. In this study, our objective is to investigate the global epidemiology of coronary heart disease from 2014 to 2023 by conducting a comprehensive bibliometric analysis of the scientific literature.  This study employs Data Collection, Data preprocessing, Co-occurrence Analysis, Co-authorship Analysis, Data Visualization and Analysis, and Ethical Consideration. The data were collected from the Scopus database and filtered by adding the keywords "coronary heart disease," "mortality," "atherosclerosis," and "hypertension" from 2014 to 2023. The study encompasses trends in publication output, Co-occurrence analysis findings, and Co-authorship analysis findings. Coronary heart disease is a major concern in global epidemiology. To guide future studies, this bibliometric analysis of Scopus data (2014-2023) examines publication trends. Findings reveal research gaps, increased publications on the disease, and decreased focus on public health. The rise in pandemic-related publications highlights its impact and viral challenges. This bibliometric analysis underscores the waning attention and research focus on coronary heart disease within the broader scope of global epidemiology. This study emphasizes the ongoing need for dedicated research to elevate global epidemiological outcomes.